LEVEL OF SERUM GAMMA GLUTAMYL TRANSFERASE IN ALCOHOLIC HEPATITIS AS A DIAGNOSTIC MARKER - M.VASANTHA; B.GAYATHRI (International Journal of Pharma and Bio Sciences, 2016)
Serum gamma glutamyl transferase (GGT or γ-GT) is a microsomal enzyme which catalyzes the transfer of the gamma-glutamyl moiety of glutathione to various peptide acceptors. It is a reliable diagnostic marker of alcohol ingestion and is one of the most sensitive and most commonly employed biochemical markers of alcohol consumption. This study was carried out with 30 alcoholic hepatitis and 30 normal non-alcoholic control subjects. The aim of this study was to establish the role of serum GGT alone in the diagnosis of alcoholic hepatitis. A significant correlation in the level of serum GGT is observed in alcoholics when compared with the normal subjects. The enzyme activity of GGT in serum is increased in average by 527.31% in the patients with alcoholic hepatitis compared to normal control subjects (p<0.05). Measurement of GGT in serum appears to be a sensitive index with low specificity in the diagnosis of alcoholics with hepatitis when correlated clinically